Infrasonic Early Warning System for Explosive Eruptions. Issue 11 (23rd November 2018) - Ripepe, M.; Marchetti, E.; Delle Donne, D.; Genco, R.; Innocenti, L.; Lacanna, G.; Valade, S.
Abstract: Explosive volcanic eruptions can eject large amounts of ash into the atmosphere, posing a serious threat to populations living near the volcano. The abrupt occurrence of such events requires a rapid response and proper volcanic hazard evaluation. Current monitoring procedures still require human intervention, which often results in significant delays between the occurrence of an eruption and notifications being dispatched. We show how dedicated infrasound array processing can be used to detect and notify the authorities, automatically and in real time, of the onset of explosive eruptions. Conceptually, our method relies on the strong coupling between infrasound and the explosive process, and it is not based on probabilistic considerations but on the ability infrasound has to detect the early stage of the explosive phase. This procedure has been tested for the last 8 years, and it is currently applied to issue early warnings for explosive eruptions at Etna Volcano. We show that the system is able to provide a prealert 1 hr before the eruption, and it has a 96.6% success rate, with only 1.7% false positive alerts and no false negative alerts. This is, to our knowledge, the first example of an operational early warning system totally based on an unsupervised algorithm that provides automatic notifications of eruptions to a government agency. We show that the same early warning concept might be applicable to arrays at large distances (>500 km), suggesting that infrasound could be successfully used to issue automatic notifications of ongoing eruptions at regional to global scales. Plain Language Summary: Most of the volcanic eruptions are rapidly evolving phenomena, strongly limiting the possibility to prompt activate emergency plans. We still lack the possibility to notify volcanic eruptions automatically, making our society highly exposed to the effects of large explosive eruptions. We present the first early‐warning system based on the acoustic waves generated by volcanic eruptions. Our approach relies on the strong coupling between sound and explosive process, and, as for the earthquake, it is not based on probabilistic consideration but on a quasi‐deterministic approach. In the last 8 years, the system was providing a prealert notification 1 hr before the eruptive onset with 96.6% rate of success, 1.7% positive false alerts, and no negative false alerts. This is, in our knowledge, the first example of an operational early‐warning system totally based on automatic and unmanned algorithm that provides automatic notification of eruption to government agency automatically and without man supervision. Early warnings can be applied even at regional distances (˃500 km), and notification of ongoing volcanic eruptions would be of valuable importance for aviation safety especially for the many active volcanoes worldwide that are still lacking of geophysical monitoring systems. Key Points: We present the first example of operational early warning for volcanic eruptions based on automatic and unsupervised algorithm The infrasound array processing detects in real‐time explosive eruptions with a 96.6% of success and no false negative alerts The early‐warning algorithm automatically delivers prealert notification 1 hr before the occurrence of the eruptive onset